PENGARUH METODE SHOW AND TELL TERHADAP KETERAMPILAN BERBICARA ANAK USIA 5-6 TAHUN DI TK XAVERIUS 3 BANDAR LAMPUNG - Sulistianah, Sulistianah; Tohir, Ahmad (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2020)
The research goal was to know the influence of Show and tell method implementation toward speaking skill on 5-6th aged in Xaverius 3 Kindergarten Bandar Lampung. The research was quasi experiment with used design one group pretest-posttest design. The researcher used saturation sampling for 30 students. The collecting data technique used pretest and posttest. The data were analyzed by t-test. Based on t-test calculation, Ha was accepted. T-score pretest and posttest result showed thit = 13.4 and ttabel= 1.69 (thit> ttabel ). Based on the result, there was influence of show and tell toward speaking skill on 5-6th in Xaverius 3 Kindergarten Bandar Lampung.Keywords: Show and tell Method, Speaking Skill.